Analysis of Hospital Emergency Department Performance Measurement with Balanced Scorecard - Hilda Melissa; Masyitoh Basabih (Syntax Corporation Indonesia, 2023)
Emergency Department (IGD) is the face of a hospital (RS). Good hospital emergency room services will result in patient satisfaction and the community around the hospital, so that the hospital becomes an option as a health facility. The performance of a hospital emergency room needs to be assessed objectively so that continuous efforts can be made to improve services. Balanced Scorecard (BSC) assessment can be used in service assessment in organizations such as hospitals or parts of organizations such as emergency room hospitals. This study aims to determine the components in emergency room services that play the most role in achieving the performance of emergency room services that support hospital performance. This research method is a scoping review using literature studies using keywords from the Balanced Scorecard AND Hospital AND Emergency with literature search strategies from the databases Ebsco Host, Embase, Scopus, Pubmed, Proquest, and Google Scholar. The results of the study contained 6 (six) appropriate articles after screening using PRISMA 2020 Flow Diagram. BSC either independently or combined with other methods can be used as performance monitoring in the health sector both in hospitals and in one of the units such as the Emergency Installation. There are 4 perspectives, namely: finance, customers, internal business processes and growth learning, where it is found that the education factor of staff training is the most widely intervened approach that results in improving the performance of emergency rooms and hospital finances. Further research suggestion is that further research is needed to assess the other three factors in the Balanced Scorecard that will effectively improve performance in other units of RS.